2009
DOI: 10.1037/a0014865
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, acculturation, and mental health-seeking attitudes among people of African descent in the United States: A preliminary investigation.

Abstract: This article investigates the relationship between psychological distress, acculturation, and help-seeking attitudes among people of African descent (N ϭ 130). Psychological distress was measured using the Global Severity Index from the Brief Symptom Inventory (L. R. Derogatis & N. Melisaratos, 1983), acculturation was measured using the Measurement of Acculturation Strategies for People of African Descent (E. M. Obasi, 2005), and help-seeking attitudes were measured using the Attitudes Toward Seeking Professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 82 publications
9
77
1
1
Order By: Relevance
“…Second, the mean effect size of the 10 studies (N = 1,751) that examined the No systematic variations in the relationship of acculturation/enculturation and psychological distress/depression or self-esteem were detected by measures or sampling sources. However, Obasi and Leong's (2009) study, which was the only study conducted with African Americans, revealed a moderately significant positive relationship between acculturation and psychological distress (r = .28). This finding was contradictory to the findings of the other studies that indicated either nonsignificant or negative associations between the two variables.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, the mean effect size of the 10 studies (N = 1,751) that examined the No systematic variations in the relationship of acculturation/enculturation and psychological distress/depression or self-esteem were detected by measures or sampling sources. However, Obasi and Leong's (2009) study, which was the only study conducted with African Americans, revealed a moderately significant positive relationship between acculturation and psychological distress (r = .28). This finding was contradictory to the findings of the other studies that indicated either nonsignificant or negative associations between the two variables.…”
Section: Resultsmentioning
confidence: 97%
“…When the correlation was reported for each subgroup of the sample (e.g., Yeh, 2003), the correlation with the overall sample was coded as the effect size. When the correlations for both acculturation/enculturation total scales and dimensions were reported, we chose the correlations with total scales (e.g., Obasi & Leong, 2009). Four studies reported only standardized regression weights without any information to calculate correlations (e.g., Cavazos-Rehg & DeLucia-Waack, 2009;Rahman & Rollock, 2004;Rodriguez, Mira, Morris, & Cardoza, 2003;Tsai et al, 2000).…”
Section: Effect Size Calculationmentioning
confidence: 99%
“…Minorities in the U.S. have historically experienced racism, discrimination, and oppression to the extent that these experiences have negatively influenced mental health help-seeking (Chung & Bemak, 2012;Obasi & Leong, 2009;Shea & Yeh, 2008). Initially developed as a concept to describe the distrust Black Americans had towards White Americans, cultural mistrust encompasses an overall mistrust of White-dominated institutions such as the legal system, educational system, job settings, and government agencies (David, 2010).…”
Section: Cultural Mistrust Of Mental Health Counselorsmentioning
confidence: 99%
“…Quantitative research in this area has also revealed blacks with high degrees of Christian Orthodoxy Mental Health, Religion & Culture 59 exhibit fewer mental-health problems than other ethnicities (Randolph-Seng, Nielsen, Bottoms, & Filipas, 2008). Other quantitative research has found blacks to be more likely to seek help from clergy than obtain professional psychological services (Allen et al, 2010;Ezemenari & Frederick, 2009;Kane, 2010;Lesniak, Rudman, Rector, & Elkin, 2006;Lewis-Coles & Constantine, 2006); forgiveness to be strongly related to the mental health of African American women (Faison, 2007); their perceived relationship with God (Hatcher, 2001); and spirituality to be strong indicators of mental health for African Americans (Ojelade, McCray, Ashby, & Meyers, 2011).…”
Section: Review Of Literature Mental Health Of African Americansmentioning
confidence: 95%